No Cure is Not Always Medical Negligence in Case of Cataract Operation: NCDRC (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
Commonly and it is more often the presumption of the patient that after any medical or surgical treatment he should get cured completely. However, the result of treatment and prognosis of disease depend upon several factors in vivo and vitro. Catena of judgments has defined the elements of medical negligence. It should be borne in mind that ‘no cure is not always medical negligence’. The complainant filed a complaint before the District Forum for alleged medical negligence from the OP- Dr. Deepak Kumar while conducting a left eye cataract operation on 30.09.2008 caused loss of vision in his left eye.
Keywords: Cataract; Cataract Compensation; Medical expert opinion; Medical negligence; Vitreous